2018
DOI: 10.3390/f9110683
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Event Simulation of Ground-Based Timber Harvesting Operations

Abstract: Operational studies are necessary to support production and management decisions of forest industries. A time study (TS) approach is widely used in timber harvesting operations to understand the performance of individual harvesting machines as well as the entire system. However, several limitations of the TS approach include the use of generalized utilization rates, incapability of capturing interactions among equipment, and model extrapolation in sensitivity analysis. In this study, we demonstrated the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Time-and-motion studies have been widely used to evaluate the performance of individual logging equipment as well as entire harvesting systems [11,12]. This type of study has been essential for predicting machine productivity and utilization rates in various scenarios under similar working conditions [13,14]. However, this approach is limited in terms of data availability due to the relatively short period of data collection and high costs of field work [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-and-motion studies have been widely used to evaluate the performance of individual logging equipment as well as entire harvesting systems [11,12]. This type of study has been essential for predicting machine productivity and utilization rates in various scenarios under similar working conditions [13,14]. However, this approach is limited in terms of data availability due to the relatively short period of data collection and high costs of field work [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This type of study has been essential for predicting machine productivity and utilization rates in various scenarios under similar working conditions [13,14]. However, this approach is limited in terms of data availability due to the relatively short period of data collection and high costs of field work [14][15][16]. Additionally, a number of past studies have assessed performance using the follow-up method, which utilizes historic output records, such as productivity and costs.…”
Section: Introductionmentioning
confidence: 99%
“…The aim in Articles III and IV was to apply a DES model which imitates reality and behaves close to reality, similarly to Windisch et al (2015). A comparison between time study and the DES approach by She et al (2018) revealed only minor differences for machine cycle times and productivity, but found that machine utilisation rates were somewhat different. However, the authors favoured DES when analysing complex systems with machine process interactions (She et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between time study and the DES approach by She et al (2018) revealed only minor differences for machine cycle times and productivity, but found that machine utilisation rates were somewhat different. However, the authors favoured DES when analysing complex systems with machine process interactions (She et al 2018). Furthermore, the DES method allowed effect of selected changes on the supply condition of forest chips to the end-using facility to be investigated without having the need for actual practical implementation of a terminal or innovative machinery on a larger scale, which would be risk and investment intensive, as well as time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…It is located on relatively flat terrain with a stand density of 865 trees ha −1 and a basal area of 34.6 m 2 ha −1 . The average tree diameter at breast height (dbh) is 22.4 cm, and the average tree height is 19.6 m. A ground-based clearcut has been a common salvage harvest practice in this area due to the high mortality rate [69]. After accounting for slope and skidding distance, a total of 627 harvest units in average size of 5.4 ha were identified as operationally feasible areas for salvage harvest [70].…”
Section: Problem Statementmentioning
confidence: 99%